Demons, gods & holly men from Indian myths & legends - Husain, Shahrukh; Das, Durga. Prasad (Eurobook Limited, 1987)
Myths and legends that reflect the richness of India's ancient civilization.
Includes index.
Keywords: Mythology, Indic -- Juvenile literature; Hindu mythology -- Juvenile literature